(untitled) (Academic Journal of Internal Affairs, 2022)
The study illustrates the complexity of the issue of football hooliganism, and highlights the innovative solutions for the treatment of it. The background of football hooliganism by presenting domestic and foreign examples, the types of supporters and spectators, and the role of private security and sports policing are observed. In the decades following the regime change, the police lost their monopoly, and private security and civil policing became more prominent in Hungary. Nowadays, the personnel of private security and civil policing are involved in the process of risk assessment of sports events, escorting and transporting groups of supporters, detaining supporters after sports events. It is important to mention sports policing, a specific part of sports administration. This narrow field can be clearly defined as specialised policing, with a set of laws regulating everything related to sports policing, complemented by the regulations of the sports federations, which also serve as guidelines for the maintenance of sports law enforcement records and the security provided at sports events. Football hooliganism is a social and sport security problem that has been present in our world for centuries, and is something that we will probably have to deal with as long as football exists. Football hooligans are a closed community, a subculture with a specific set of rules and a deep knowledge of their functioning is essential to maintain the safety of our sport events. Nowadays, the emphasis is more on understanding the processes, communication and cooperation, as well as openness to innovative solutions.